Engineering challenges in biodiesel production from microalgae. (September 2013) - Aguirre, Ana-Maria; Bassi, Amarjeet; Saxena, Priyanka
Abstract : In recent years, the not too distant exhaustion of fossil fuels is becoming apparent. Apart from this, the combustion of fossil fuels leads to environmental concerns, the emission of greenhouse gases and issues with global warming and health problems. Production of biodiesel from microalgae may represent an attractive solution to the above mentioned problems, and can offer a renewable source of fuel with fewer pollutants. This review presents a compilation of engineering challenges related to microalgae as a source of biodiesel. Advantages and current limitations for biodiesel production are discussed; some aspects of algae cells biology, with emphasis on cell wall composition, as it represents a barrier for fatty acid extraction and lipid droplets are also presented. In addition, recent advances in the different stages of the manufacturing process are included, starting from the strain selection and finishing in the processing of fatty acids into biodiesel.